15N NMR Hyperpolarization of Radiosensitizing Antibiotic Nimorazole by Reversible Parahydrogen Exchange in Microtesla Magnetic Fields. Issue 5 (1st December 2020) - Salnikov, Oleg G.; Chukanov, Nikita V.; Svyatova, Alexandra; Trofimov, Ivan A.; Kabir, Mohammad S. H.; Gelovani, Juri G.; Kovtunov, Kirill V.; Koptyug, Igor V.; Chekmenev, Eduard Y.
Abstract: Nimorazole belongs to the imidazole‐based family of antibiotics to fight against anaerobic bacteria. Moreover, nimorazole is now in Phase 3 clinical trial in Europe for potential use as a hypoxia radiosensitizer for treatment of head and neck cancers. We envision the use of [ 15 N3 ]nimorazole as a theragnostic hypoxia contrast agent that can be potentially deployed in the next‐generation MRI‐LINAC systems. Herein, we report the first steps to create long‐lasting (for tens of minutes) hyperpolarized state on three 15 N sites of [ 15 N3 ]nimorazole with T1 of up to ca. 6 minutes. The nuclear spin polarization was boosted by ca. 67000‐fold at 1.4 T (corresponding to P 15N of 3.2 %) by 15 N− 15 N spin‐relayed SABRE‐SHEATH hyperpolarization technique, relying on simultaneous exchange of [ 15 N3 ]nimorazole and parahydrogen on polarization transfer Ir‐IMes catalyst. The presented results pave the way to efficient spin‐relayed SABRE‐SHEATH hyperpolarization of a wide range of imidazole‐based antibiotics and chemotherapeutics. Abstract : Synthesis of 15 N3 ‐enriched antibiotic and hypoxic radiosensitizer nimorazole is reported. Spin‐relayed signal amplification by reversible exchange in microtesla magnetic field yielded up to 3.2 % 15 N nuclear spin polarization with relaxation time constant of 5.9±0.2 min at 1.4 T. The isomer of nimorazole formed in the synthesis was also hyperpolarized indicating that this approach can be extended to a wide range of nitroimidazole‐based drugs.